Correlation of gene methylation in surgical margin imprints with locoregional recurrence in head and neck squamous cell carcinoma. Issue 12 (13th March 2015) - Hayashi, Masamichi; Wu, Gaosong; Roh, Jong‐Lyel; Chang, Xiaofei; Li, Xiufeng; Ahn, Julie; Goldsmith, Marla; Khan, Zubair; Bishop, Justin; Zhang, Zhe; Zhou, Xian Chong; Richmon, Jeremy; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Securing negative surgical margins is a critical goal for head and neck surgery. Local recurrence develops even in some patients who have histologically negative surgical margins. Minimal residual tumor cells may lead to locoregional recurrence despite clear histologic margins reported at the time of resection of head and neck squamous cell carcinoma (HNSCC). To identify subclinical residual disease, the authors analyzed deep margin imprint samples collected on 1‐layer nitrocellulose sheets. METHODS Bisulfite‐treated DNA samples from 73 eligible patients were amplified by quantitative methylation‐specific polymerase chain reaction (QMSP) targeting 6 genes (deleted in colorectal cancer [DCC], endothelin receptor type B [EDNRB], homeobox protein A9 [HOXA9], kinesin family member 1A [KIF1A], nidogen‐2 [NID2], and N‐methyl D‐aspartate receptor subtype 2B [NR2B]). QMSP values were dichotomized as positive or negative. Associations between the QMSP status of deep margin samples and clinical outcomes were evaluated. RESULTS Two‐gene methylation combinations among the genes DCC, EDNRB, and HOXA9 were associated with decreased locoregional recurrence‐free survival, recurrence‐free survival, and overall survival. The methylated gene combination of EDNRB and HOXA9 in margin imprints was the most powerful predictor of poor locoregional recurrence‐free survival (hazard ratio [HR], 3.31; 95% confidence interval [CI], 1.30‐8.46; P = .012) independent of standard histologic factors. In addition, methylation of both EDNRB and HOXA9 indicated a trend toward reduced recurrence‐free survival (HR, 2.74; 95% CI, 0.90‐8.33; P = .075) and reduced OS (HR, 5.78; 95% CI, 0.75‐44.7; P = .093) in multivariable analysis. CONCLUSIONS A panel of gene methylation targets in deep surgical margin imprints provides a potential predictive marker of postoperative locoregional recurrence. Intraoperative use of molecular margin imprint analysis may assist surgeons in obtaining rigorously negative surgical margins and improve the outcome of head and neck surgery. Cancer 2015;121:1957–1965. © 2015 American Cancer Society.